PENDEKATAN EPIDEMIOLOGI MENGATASI MASALAH SUPERBAKTERI MELALUI PUSKESMAS DAN RUMAH SAKIT - Alib Birwin; Buchari Lapau (Institut Kesehatan dan Teknologi Al Insyirah, 2018)
Super Bacteria is resistant bacteria to all antibiotics. Its health care is expensive but it causes many deaths. The objective of this paper is to show information how to use the epidemiological approach in the prevention and treatment of Super Bacteria through health center and hospital. Epidemiology has 2 strategies namely epidemiological surveillance and research achieving its objectives, one of which is a natural history of disease consisting of pre-pathogenesis and pathogenesis periods. In the prepathogenesis period, primary prevention conducted on Knot 1 including bacteria, and on Knot 2 namely the environment transmitting the bacteria. In the pathogenesis periode, secondary prevention conducted on Knot 3 namely factors in and out of human body causing bacterial diseases detected by early diagnosis. Epidemiological Surveillance produces information to achieve its objective namely early warning system for the prevention of bacterial diseasesandthe failure of treatment causing resistant bacteria and Super Bacteria. Another objective of surveillance is to monitor and evaluate apreventive program for bacterial disease. Indonesian researcher is expected to conduct medical laboratory research on crocodilelocatedin Komodo island to find new antibiotic killing resistant bacteria and SuperBacteria, continued epidemiological experiment to detect efficacy of the new treatment